Institutional trust and alcohol consumption in Sweden: The Swedish National Public Health Survey 2006 - Lindström Martin; Ahnquist Johanna; Wamala Sarah P (BMC, 2008)
Abstract Background Trust as a measure of social capital has been documented to be associated with health. Mediating factors for this association are not well investigated. Harmful alcohol consumption is believed to be one of the mediating factors. We hypothesized that low social capital defined as low institutional trust is associated with harmful alcohol consumption. Methods Data from the 2006 Swedish National Survey of Public Health were used for analyses. The total study population comprised a randomly selected representative sample of 26.305 men and 30.584 women aged 16-84 years. Harmful alcohol consumption was measured using a short version the Alcohol Use Disorders Identification Test (AUDIT), developed and recommended by the World Health Organisation. Low institutional trust was defined based on trust in ten main welfare institutions in Sweden. Results Independent of age, country of birth and socioeconomic circumstances, low institutional trust was associated with increased likelihood of harmful alcohol consumption (OR (men) = 1.52, 95% CI 1.34-1.70) and (OR (women) = 1.50, 95% CI 1.35-1.66). This association was marginally altered after adjustment for interpersonal trust. Conclusion Findings of the present study show that lack of trust in institutions is associated with increased likelihood of harmful alcohol consumption. We hope that findings in the present study will inspire similar studies in other contexts and contribute to more knowledge on the association between institutional trust and lifestyle patterns. This evidence may contribute to policies and strategies related to alcohol consumption.